LEARNING MEDIA THAT IMPROVE SOLAR SYSTEM LEARNING OUTCOMES - Linda Susanti; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the differences in learning outcomes between students using video and those using e-books, as well as the impact of learning motivation on understanding the Solar System material. The research design employs a quasi-experimental approach involving 42 sixth-grade students from SD Negeri Rejosopinggir. The results indicate that the use of video significantly enhances students' learning outcomes, with an average posttest score of 82.9 compared to 78.3 for the e-book group. Additionally, students with high motivation show a greater score increase. These findings suggest that learning media should be tailored to students' motivation levels to achieve optimal learning outcomes.